Relationship between neutrophil-lymphocyte ratio and platelet-lymphocyte ratio with the severity of COVID-19 - Arini, Ida A.; Masyeni, Sri; Widhidewi, Ni W. (Narra Sains Indonesia, 2024)
Coronavirus disease 2019 (COVID-19) is an infectious disease that spreads rapidly causing a high case fatality rate in vulnerable populations. Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) are known to be inflammatory biomarkers in certain infections. The aim of this study was to determine the relationship between NLR and PLR with the severity of COVID-19. A cross-sectional study was conducted at Tabanan Regency General Hospital, Bali, Indonesia, from January 2021 to December 2022. All patients included in the study tested positive for COVID-19 by real-time polymerase chain reaction (RT-PCR), aged 18–50 years with no comorbid. Laboratory examinations were carried out on admission. The patients were categorized into two groups based on the severity: moderate and severe/critical. The Mann-Whitney test was used to determine the association between NLR and PLR with the severity of COVID-19. A total of 104 patients were included in the study, the majority of COVID-19 patients had moderate (77.9%) severity. The average NLR was 5.8 and the PLR was 21.7. There was a significant relationship between NLR (p=0.002) and PLR (p=0.001) with the severity of COVID-19. The defined cut-off values of NLR and PLR were ≥3.8 and ≥106, yielding sensitivities of 95% and 70%, and specificities of 74% and 50%, respectively. This study highlights the promising role of NLR and PLR as predictive biomarkers to assess COVID-19 severity.